Biostimulants isolated or integrated with paclobutrazol as tomato development triggering factors - Silva, Talles Victor; Melo, Hyrandir Cabral de; Tarazi, Monita Fiori de Abreu; Junior, Luis Carlos Cunha; Campos, Luiz Fernandes Cardoso; Nascimento, Abadia dos Reis (Emirates Journal of Food and Agriculture, 2020)
Plant biostimulants are substances with different chemistry or biological composition whose, when applied to plants, can favour their development mainly by enhance nutrient uptake or nutrition efficiency and also can alter plant hormonal balance. Paclobutrazol (PBZ) is a retardant plant growth regulator which promotes reduction on stem internodes culminating in shorter plants. The integration of both, biostimulants and PBZ, can lead better development of plants by at same time favour the nutrition performance of shorter plants. Although some farmers already have used these substances in crop field, alone or in combination, there is a great lack of scientific studies to verify the real efficiency of the biostimulants available in market. The aim of this study was to study the effect of different biostimulants on the morphometrical and physiological aspects of tomato when applied in combination or not with paclobutrazol in Solanum lycopersicum L., hybrid H9553. The biostimulants used were Stimulate®, Serenade®, EnerVig®, Px-Fertil®, Vorax®, Liqui-plex® and DuoOrgano+®. PBZ reduced plant height and, unlike expected, no one of the biostimulants favoured volume increase or dry mass of roots. However, all biostimulants favoured the accumulation of leaf dry mass, with no increase in the number of leaves or net photosynthetic rate per specific leaf area. When isolated, or in interaction with biostimulants, the PBZ generated stimulatory or inhibitory effect on expression of the parameters evaluated, depending on the organ and its age, and acted in synergism or antagonism with the biostimulants, depending on the substance in question.